Qualitative and quantitative ultrasound analysis of oropharyngeal swallowing - Rocha, Simone Galli [UNESP]; Silva, Roberta Gonçalves da [UNESP]; Berti, Larissa Cristina [UNESP] (FapUNIFESP (SciELO), 2015)
Purpose: To analyze the effect of the age group and food's consistency according to the qualitative and quantitative ultrasonographic parameters in the oropharyngeal swallowing. Methods: Ultrasonographic evaluations of swallowing were performed in 100 health individuals (divided into four groups, whose age brackets were 20-60 years), using liquid and mashed consistencies. For qualitative analysis, five steps were taken into account during the oropharyngeal swallowing. The following parameters were regarded in the quantitative analysis: duration of the tongue propulsion and maximum displacement of the hyoid bone during swallowing. Results: In the qualitative ultrasonographic analysis, all the participants, independent to age groups, presented the same pattern of the tongue position (1, 2, and 5 phases), whereas in phase 3 there was a great variability within participants of the wavelike movement of the tongue. In phase 4, the displacement of the hyoid bone increased as a consequence of the consistency of the food. In the quantitative ultrasonographic analysis, a significant effect regarding age (p=0.03), consistence (p=0.00), as well as the age*consistency interaction was observed (p=0.03). Overall, the group of individuals between 20 and 30 years (G1) differed from the other groups and pudding consistency increased the measure of duration and displacement. Conclusion: The ultrasonography of the movement of the tongue proved itself as a viable instrument to describe the oropharyngeal swallowing. Parameters such as age and food consistency modify the USG images of movement of the tongue in normal subjects should be considered in ultrasound examination of oropharyngeal swallowing.
Keywords: Evaluation; Qualitative Analysis; Swallowing; Ultrasonography